Ligature‐associated bacterial profiles are linked to type 2 diabetes mellitus in a rat model and influenced by antibody treatment against TNF‐α or RAGE. Issue 1 (February 2017) - Grauballe, M.B.; Belstrøm, D.; Østergaard, J.A.; Paster, B.J.; Schou, S.; Flyvbjerg, A.; Holmstrup, P.
Abstract: There is a bidirectional relationship between periodontal disease (PD) and type 2 diabetes mellitus (T2D). T2D may lead to ecological perturbations in the oral environment, which may facilitate an altered microbiota. However, previous studies have been inconclusive in determining the effect of T2D on oral bacterial profiles. Therefore, we aimed to evaluate the influence of T2D on the ligature‐associated bacterial profile in a diabetic rat model with PD and investigated the impact of blocking inflammatory pathways with antibodies targeting either Tumor Necrosis Factor α (TNF‐α) or the receptor of advanced glycation end‐products (RAGE). A total of 62 Zucker obese rats (45 T2D) and 17 lean (non‐T2D) were divided into 4 treatment groups; lean with PD, obese with PD, obese with PD and anti‐TNF‐α treatment, and obese with PD with anti‐RAGE treatment. Periodontal disease was ligature induced. Ligature‐associated bacterial profiles were analyzed using Human Oral Microbe Identification Microarray (HOMIM). Ligature‐associated bacterial profiles differed between lean and obese rats. Furthermore, treatment with antibodies against TNF‐α or RAGE had an impact on subgingival bacterial profiles. T2D phenotypes are associated with different ligature‐associated bacterial profiles and influenced by treatment with antibodies against TNF‐α or RAGE.